1988
DOI: 10.1016/0042-6822(88)90512-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of mouse hepatitis virus A59 mRNA 2: Indications for RNA recombination between coronaviruses and influenza C virus

Abstract: The nucleotide sequence of the unique region of coronavirus MHV-A59 mRNA 2 has been determined. Two open reading frames (ORF) are predicted: ORF1 potentially encodes a protein of 261 amino acids; its amino acid sequence contains elements which indicate nucleotide binding properties. ORF2 predicts a 413 amino acids protein; it lacks a translation initiation codon and is therefore probably a pseudogene. The amino acid sequence of ORF2 shares 30% homology with the HA1 hemagglutinin sequence of influenza C virus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
219
0
4

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(228 citation statements)
references
References 58 publications
5
219
0
4
Order By: Relevance
“…The observation that the nucleotide sequence of the S gene encoding amino acids 470 to 480 (data not shown) is highly homologous (81 ~) between BECV and MHV-A59 and does not exist in MHV-JHM leads us to propose the occurrence of deletions in this genome segment. Our suggestion is supported by the identification of a functional HA gene in BECV (Parker et al, 1989) whereas only a related HA pseudogene was identified in MHV-A59 (Luytjes et al, 1988); this HA is most likely to occur if the BECV genome is more closely related to a possible common ancestor.…”
Section: Llafnqdgvifnavdcksdfmseikcktlsiapstgvyel310supporting
confidence: 57%
See 1 more Smart Citation
“…The observation that the nucleotide sequence of the S gene encoding amino acids 470 to 480 (data not shown) is highly homologous (81 ~) between BECV and MHV-A59 and does not exist in MHV-JHM leads us to propose the occurrence of deletions in this genome segment. Our suggestion is supported by the identification of a functional HA gene in BECV (Parker et al, 1989) whereas only a related HA pseudogene was identified in MHV-A59 (Luytjes et al, 1988); this HA is most likely to occur if the BECV genome is more closely related to a possible common ancestor.…”
Section: Llafnqdgvifnavdcksdfmseikcktlsiapstgvyel310supporting
confidence: 57%
“…1 b). Luytjes et al (1987Luytjes et al ( , 1988 put forward two hypotheses to account for the difference between MHV-A59 and MHV-JHM in this domain of the S protein. The first hypothesis is that the MHV-JHM genome is deleted with respect to a nucleotide sequence corresponding to amino acids 453 to 545 of the S protein of MHV-A59; the second is that the MHV-A59 genome has acquired genomic material by non-homologous recombination.…”
Section: Llafnqdgvifnavdcksdfmseikcktlsiapstgvyel310mentioning
confidence: 99%
“…Sequence analysis of the unique region of mRNA 2 of MHV strain A59 has revealed two ORFs (ORF 1 and ORF 2; Luytjes et al, 1988). A 30K protein has been predicted on the basis of the ORF 1 sequence and was detected in MHV-infected cells by antiserum raised against an expression product of ORF 1 (P. Bredenbeek, A. Noten & W. Spaan, unpublished observations).…”
Section: Binns T D K Brown and S C Inglis Personal Communicationmentioning
confidence: 99%
“…Comparison of this ORF with sequences held in the EMBL database reveals remarkably high identity to the FIPV spike glycoprotein-encoding sequences (91.1 ~) and, to a lesser degree, the porcine virus S genes ( Table 1), indicating that this is the CCV S gene. In some strains of MHV, the haemagglutinin-esterase glycoprotein gene (HE) is found downstream of the polymerase gene (Luytjes et al, 1988) but it is clear that CCV, like TGEV and IBV, encodes only the polymerase gene upstream of the S gene (Britton & Page, 1990;Boursnell et al, 1987).…”
Section: Orfs Encoded By Mrnas 1 Andmentioning
confidence: 99%